Current Trends to Overcoming Threats to Economic Security In Agricultural Production Cooperatives - Alevtina Vasilievna KOROTKOVA; Larisa Vitalyevna BAKULEVSKAYA; Evgeniy Alekseevich IVANOV; Lyudmila Mikhailovna KORNILOVA; Marina Sergeevna ABROSIMOVA; Maria L. TOLSTOVA; Nikolay Nikolaevich PUSHKARENKO (Communications of International Proceedings, 2021)
Being a part of the economy, agriculture and agrarian production follow its fundamental laws that are present in any economic system, yet, when carrying out economic and business activity in agriculture, we must bear in mind specifics of production techniques, location of production, labor and land resources. Agricultural production cooperative uses land resources and other weather and climate-dependent natural resources as its input supplies. Currently, facilitating the economic security of agricultural production cooperatives is among the important tasks of agricultural industry.
Keywords: Economic Security; Overcome Threats; Threats to Economic Security; Agricultural Production Cooperative